Experimental validation of the kinematic design of 3-PRS compliant parallel mechanisms. (November 2016) - Ruiz, A.; Campa, F. J.; Roldán-Paraponiaris, C.; Altuzarra, O.; Pinto, C.
Abstract: In this paper, a procedure for the kinematic design of a 3-P RS compliant parallel manipulator of 3 degree of freedom is proposed. First, under the assumption of small displacements, the solid body kinematics of the 3-P RS has been studied, performing a comprehensive analysis of the inverse and forward kinematic problem, and calculating the rotations that the revolute and spherical flexure joints must perform. Then, after defining some design requirements and therefore the necessary displacements to fulfill, a design process based on the finite element calculations has been stablished, giving the necessary guidelines to reach the optimal solution on a 3-P RS compliant mechanism. Also, a prototype has been tested, using a coordinate measuring machine to verify its dimensions and the resulting displacements in the end effector and the actuated joints. Finally, those measurements have been compared with the FEM and the rigid body kinematics predictions, contrasting the validity of those two modelling approaches for the kinematic design of compliant mechanisms.